ORIGIN OF PALEOPROTEROZOIC KOMATIITES AT JEESIOROVA, KITTILA GREENSTONE COMPLEX, FINNISH LAPLAND - Gangopadhyay A.; Walker R.J.; Hanski E.; Solheid P.A. (My University, 2006)
Komatiites from the ?2?Ga Jeesiorova area in Finnish Lapland have subchondritic Al2O3/TiO2 ratios like those in Al-depleted komatiites from Barberton, South Africa. They are distinct in that their Al abundances are higher than those of the Al-depleted rocks and similar to levels in Al-undepleted komatiites. Moderately incompatible elements such as Ti, Zr, Eu, and Gd are enriched. Neither majorite fractionation nor hydrous melting in a supra-subduction zone setting could have produced these komatiites. Their high concentrations of moderately incompatible elements may have resulted from contamination of their parental melt through interaction with metasomatic assemblages in the lithospheric mantle or enrichment of their mantle source in basaltic melt components. Re–Os isotope data for chromite from the Jeesiorova rocks yield an average initial 187Os/188Os of 0·1131 ± 0·0006 (2?), ?Os(I) = 0·1 ± 0·5. These data, coupled with an initial ɛNd of ?+4, indicate that melt parental to the komatiites interacted minimally with ancient lithospheric mantle. If their mantle source was enriched in a basaltic component, the combined Os–Nd isotopic data limit the enrichment process to within ?200?Myr prior to the formation of the komatiites. Their Os–Nd isotopic composition is consistent with derivation from the contemporaneous convecting upper mantle.
Keywords: Finnish Lapland; Jeesiorova; komatiites; mantle geochemistry; petrogenesis; redox state; Re/Os isotopes; Ti enrichment; Докембрий::Протерозой::Палеопротерозойская; Precambrian::Proterozoic::Paleoproterozoic